Professional Status: Teachers' Difficulties in Compiling Questions Based on Higher Order Thinking Skills - Pramesti, Ni Ketut Ayu; Riastini, Putu Nanci (International Journal of Elementary Education, 2023)
Higher-order thinking skills are needed in dealing with 21st-century learning. The teacher's role is crucial in improving students' higher-order thinking skills. However, implementing HOTS-based questions is rarely used by teachers who have or have not held professional status. This study analyzes teachers' difficulties in compiling HOTS-based questions regarding professional status. This study used a descriptive quantitative approach. The population in this study were all teachers in Cluster. Sampling in this study was carried out by cluster sampling, then proportional random sampling in each Cluster. The sample in this study was 34 teachers, who were divided into two groups, namely teachers who had not yet held professional status and had. Data collection used an instrument in the form of a questionnaire. Data were analyzed using descriptive statistics in mean, standard deviation, and percentages converted to PAP. The results of this study were that teachers who are not yet professional in compiled HOTS-based questions were in the very high category, while the difficulties of teachers who already hold professional status in compiled HOTS-based questions were in the high category. Teachers who are not yet professional in compiling HOTS-based questions have difficulty understanding cognitive levels, determining cognitive levels, choosing KKO, and compiling contextual stimuli. For teachers with professional status, the difficulties experienced are chosen KKO, compiled contextual stimuli, and compiled stimuli that are easy for students to understand.